Thomas O'Dea's Dilemmas of Institutionalization: A Case Study and Re-evaluation after Twenty-five Years - Mathisen, James A. (Sociological analysis, 1987)
From 1961 when O'Dea first published his model of the five dilemmas through 1983 when his The Sociology of Religion appeared in a revised edition and the dilemmas were restated virtually intact, little critical attention has been paid to his description, despite the model's being incorporated into much of the theoretical literature in the sociology of religion. One might say that the dilemmas of institutionalization have been institutionalized.This paper applies the dilemmas to gain an understanding of the institutionalization process in a specific organization, the Moody Bible Institute of Chicago, as representative of the religious movement of Fundamentalism. After an historical examination of Moody over four periods of time, the conclusion is drawn that although the model of the five dilemmas provides some descriptive insight, it is not adequate as a theory of the middle range to provide the understanding of institutionalization which O'Dea sought.